Impact of Early Life Nutrition on Children’s Immune System and Noncommunicable Diseases Through Its Effects on the Bacterial Microbiome, Virome and Mycobiome - Fragkou, Paraskevi C.; Karaviti, Dareilena; Zemlin, Michael; Skevaki, Chrysanthi (Frontiers in Immunology, 2021)
The first 1000 days of life, including the intrauterine period, are regarded as a fundamental stepping stone for the development of a human. Unequivocally, nutrition during this period plays a key role on the proper development of a child, both directly through the intake of essential nutrients and indirectly by affecting the composition of the gut microbiota. The gut microbiota, including bacteria, viruses, fungi, protists and other microorganisms, is a highly modifiable and adaptive system that is influenced by diet, lifestyle, medicinal products and the environment. Reversely, it affects the immune system in multiple complex ways. Many noncommunicable diseases (NCDs) associated with dysbiosis are “programmed” during childhood. Nutrition is a potent determinant of the children’s microbiota composition and maturation and, therefore, a strong determinant of the NCDs’ programming. In this review we explore the interplay between nutrition during the first 1000 days of life, the gut microbiota, virome and mycobiome composition and the development of NCDs.